Debating witchcraft in Africa : the "Magritte Effect" - Péclard, Didier; Warnier, Jean-Pierre (Langaa RPCIG, 2018)
Given the circularity of the witchcraft complex in Africa, given its performative potential, isn't the flood of anthropological publications on the topic counter-productive insofar as it feeds what it pretends to analyse, and even stigmatize? Wouldn't the social scientists be well advised not to emulate the media and the Evangelical preachers and to avoid bestowing on Africa the dubious privilege of being no more than a shadow theatre devoid of substance on the stage of which everything--power, work, production, economy, the family--would actually be played in the occult? In this publication, eight scholars--namely: Jean-Pierre Warnier, Didier Péclard, Julien Bonhomme, Patrice Yengo, Jane Guyer, Joseph Tonda, Francis Nyamnjoh and Peter Geschiere--engage in a lively and contradictory debate on witchcraft/sorcery in Africa in a controversial historical context.